Disclosing the Molecular Link between Apospory and Diplospory - Garbus, Ingrid (2021)
Gametophytic apomixis forms seeds with clonal embryos identical to the mother plant through two different mechanisms, namely apospory and diplospory, both of them involving the formation of nonreduced megagametophytes within the ovule. These nonreduced embryo sacs are originated from companion nucellar cells (apospory) or the megaspore mother cell, after absence/failure of meiosis (diplospory). In both paths the nonreduced egg cells produce embryos through parthenogenesis. Our hypothesis here was that, at least for some candidate genes, apomeiosis and parthenogenesis associate, respectively, with contrasting or identical representation patterns in aposporous vs. diplosporous differential mRNA expression comparisons. The rationale supporting this proposition is that in aposporous and diplosporous plants apomeiosis might involve some common genes under an opposite spatio-temporal regulation pattern (OE transcripts), while parthenogenesis should be identically activated in both reproductive types (IE candidates). We compared two sets of Roche/454 sequences differentially expressed in reproductive organs of sexual vs. apomictic plants of Paspalum notatum (aposporous) and Eragrostis curvula (diplosporous) from premeiosis to anthesis, to identify OE and IE transcripts. Then, the selected sequences were investigated in TruSeq/Hiseq Illumina RNA floral libraries constructed at different reproductive stages. We found 89 opposite expression transcripts exclusively represented at premeiosis and 66 equal expression transcripts occurring at anthesis only. These candidate genes were used to produce String interaction networks with others previously related with apomeiosis and parthenogenesis, and their location is being mapped within the Paspalum and Eragrostis genomic ACL (apomixis controlling loci). Functional analysis of selected sequences is at work.